Back Cover: The Origin of Quantum Effects in Low‐Dimensional Thermoelectric Materials (Adv. Quantum Technol. 1/2021). Issue 1 (15th January 2021) - Hung, Nguyen T.; Saito, Riichiro
Abstract : In article number 2000115, Nguyen Tuan Hung and Riichiro Saito report on the origin of the quantum effects to improve the thermoelectricity of low‐dimensional materials. The power factor enhances when the confinement length (diameter of 1D materials or the thickness of 2D materials) is smaller than the thermal de Broglie wavelength, which is established as a crucial parameter to enhance the thermoelectricity. The cover image depicts electrons moving from hot to cold temperature, which can generate electrical energy. The quantum effect occurs when the width of the system is smaller than the thermal de Broglie wavelength.